Reinterpretation of Islamic Law: The Practice of Sirri Marriage Among University Students In Indonesia - Wandri, Amra; Ismail, Ismail; Asasriwarni, Asasriwarni (GIC Proceeding, 2024)
This research explores the phenomenon of "Sirri marriage" (unregistered Islamic marriages) among university students in Indonesia, shedding light on the evolving dynamics of Islamic law interpretation in contemporary society. The study employs a qualitative approach, utilizing interviews, surveys, and document analysis to investigate the motivations, perceptions, and consequences of students engaging in Sirri marriage. By examining the socio-cultural factors influencing this practice, the research aims to contribute to a deeper understanding of how Islamic legal principles are reinterpreted and negotiated within the context of modern higher education. The findings provide insights into the complexities surrounding Sirri marriage, addressing both the challenges it poses to traditional legal frameworks and its potential impact on the broader discourse on Islamic jurisprudence in Indonesia. This study contributes to the ongoing dialogue on the adaptation of Islamic law to contemporary realities, emphasizing the need for nuanced perspectives that account for the diverse ways in which individuals navigate their religious and social identities.